2018
DOI: 10.1007/s00038-018-1085-7
|View full text |Cite
|
Sign up to set email alerts
|

Marketing techniques in television advertisements of food and drinks directed at children in Spain, 2012

Abstract: There is an extensive use of marketing techniques in television AFDs directed to children in Spain. Most products advertised were unhealthy, so stronger governmental regulations are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…It has been shown that foods advertised to children in different media are mostly products with less favourable nutritional compositions, which should be avoided in the context of a healthy diet [8,9,10,11,12]. Consequently, several countries have already adopted policies restricting children’s exposure to the marketing of less-healthy foods [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that foods advertised to children in different media are mostly products with less favourable nutritional compositions, which should be avoided in the context of a healthy diet [8,9,10,11,12]. Consequently, several countries have already adopted policies restricting children’s exposure to the marketing of less-healthy foods [13].…”
Section: Introductionmentioning
confidence: 99%
“…Marketing and nutritional information powerfully influence food choices. Food marketing is a powerful driver of ultra-processed food consumption campaigns,35 36 with social and new media resulting in a closer interaction between consumers and brands 37–39. This is a potential policy area to develop in Brazil, building on an initiative such as the UK national 21:00 TV ban or advertising in public transport in London 40.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, little is known or monitored about the abusiveness of food advertising worldwide. As far as we are aware, most of the studies that analysed food advertising on TV focused their attention on advertising strategies ( Gómez et al ., 2017 ; León-Flández et al ., 2018 ; Kent et al ., 2011 ) rather than assessing abusive characteristics regarding current regulations. Even research from other countries that applied the INFORMAS protocol ( Kelly et al ., 2015 ; Allemandi et al ., 2018 ) did not approach the topic of abusive and misleading ads.…”
Section: Discussionmentioning
confidence: 99%